An enhanced BAM for unbounded or partially bounded CRS additive models. (October 2015) - Pastor, Jesus T.; Aparicio, Juan; Alcaraz, Javier; Vidal, Fernando; Pastor, Diego
Abstract: The Bounded Adjusted Measure (BAM), initially defined for the additive model, which is a variable returns to scale (VRS) model, was extended to the constant returns to scale (CRS) case[7] . The added range-bounds, which maintain unaltered the production possibility set (PPS) under VRS, showed an influential effect under CRS, reducing the corresponding PPS, as well as a negative effect, excluding some of the original CRS projections. Here we propose an enhanced extension that, by considering a different set of less restrictive bounds, eliminates the negative effect. Moreover, we customize this new extension for the family of partially bounded CRS additive models, i.e., models where at least one variable is naturally bounded from below, if it is an input, or from above, if it is an output. Highlights: The Bounded Adjusted Measure for CRS additive models is enhanced. 'Comprehensive' bounds for unbounded inputs and outputs are calculated. How to work with naturally bounded inputs and outputs is shown. The new approach is illustrated through a numerical example.